Analysis of elderly health care in Mongolia - ENKHBAYAR, Purevsuren (KDI School, 2021)
The purpose was to provide an overview of the main issues related to aging and health of elderly in Mongolia. The Mongolia is located in north east Asia with just more than 3,200,000 population. In 2020, the average life expectancy at birth was 70.71 years, an increase of 1.14 years over the previous five years. In 2020, the gender gap in life expectancy at birth was 9.5 years. The total number of older persons who had outpatient examinations in 2017 was 3.1 million (in repeated numbers). Of the total number of outpatients examined, 38.7 percent were men and 61.3 percent were women. In terms of age groups, 34.6 percent are between the ages of 55 and 59, 27.8 percent are between the ages of 60 and 64, and 37.6 percent are 65 and over. Cardiovascular diseases account for about 35.1 percent, 12.6 percent for gastrointestinal diseases, 10.3 percent for urinary tract system diseases and neurological diseases about 8.7 percent of the total hospitalized elderly. In Mongolia, long-term care for the elderly and disabled is weak, as most long-term care is provided unofficially within the family. The country has attempted to address issues related to limited capacity and lack of cross-sector cooperation and unmet elderly needs.
Thesis(Master) -- KDI School: Master of Development Policy, 2021
Keywords: Older people--Medical care--Mongolia